Changing HIV treatment eligibility under health system constraints in sub-Saharan Africa: investment needs, population health gains, and cost-effectiveness - Hontelez, Jan A.C. (AIDS, 2016)
OBJECTIVE: We estimated the investment needs, population health gains, and cost-effectiveness of different policy options for scaling-up prevention and treatment of HIV in the 10 countries that currently comprise 80% of all people living with HIV in sub-Saharan Africa (Ethiopia, Kenya, Malawi, Mozambique, Nigeria, South Africa, Tanzania, Uganda, Zambia, and Zimbabwe). DESIGN: We adapted the established STDSIM model to capture the health system dynamics: demand-side and supply-side constraints in the delivery of antiretroviral treatment (ART). METHODS: We compared different scenarios of supply-side (i.e. health system capacity) and demand-side (i.e. health seeking behavior) constraints, and determined the impact of changing guidelines to ART eligibility at any CD4(+) cell count within these constraints. RESULTS: Continuing current scale-up would require US$178 billion by 2050. Changing guidelines to ART at any CD4(+) cell count is cost-effective under all constraints tested in the model, especially in demand-side constrained health systems because earlier initiation prevents loss-to-follow-up of patients not yet eligible. Changing guidelines under current demand-side constraints would avert 1.8 million infections at US$208 per life-year saved. CONCLUSION: Treatment eligibility at any CD4(+) cell count would be cost-effective, even under health system constraints. Excessive loss-to-follow-up and mortality in patients not eligible for treatment can be avoided by changing guidelines in demand-side constrained systems. The financial obligation for sustaining the AIDS response in sub-Saharan Africa over the next 35 years is substantial and requires strong, long-term commitment of policy-makers and donors to continue to allocate substantial parts of their budgets.